Solve, showing all steps: 5(x – 3) – 2(2x + 4) = -2(x – 2)

QUESTION POSTED AT 01/06/2020 - 04:00 PM

Answered by admin AT 01/06/2020 - 04:00 PM

Distribute:
5(x-3) -2 (2x+4) = -2(x-2) becomes ---> 5x-15 -4x-8 = -2x+4
Add like terms:
5x-15 -4x-8  becomes ---> -x-23
Bring the -23 to the right side leaving you with:
-x= -2x+ 27
Bring the -2x to the left side leaving you with:
x=27
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

Graph the exponential function. y = 4(3) x

QUESTION POSTED AT 02/06/2020 - 01:30 AM